The drivers of emission reductions in the European carbon market - Hilde Christiane Bjørnland; Jamie Cross; Felix Kapfhammer (Norges Bank, 2024)
This paper studies the drivers of emission reductions in the carbon market of the European Union Emission Trading System (EU ETS) since its inception in 2005. We introduce a novel empirical framework that facilitates the joint identification of simultaneous demand and supply shocks underlying the European carbon market. We find that emission supply restrictions of the EU ETS were the dominant driver of emissions reductions, reducing emissions by 46%. However we also find that two opposing emission demand factors also played an important role. Demand from industrial economic activity increased emissions by 15%, while other demand-side factors, primarily reflecting the transition to low-carbon economies, reduced emissions by 21%.
hdl:11250/3172089
Keywords: Q41; Q54; Q58; 330; climate policy; carbon pricing; emission trading system; cap and trade; demand and supply